1997
DOI: 10.1161/01.str.28.10.2060
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Motor Impairment and Infarct Volume After Permanent and Transient Middle Cerebral Artery Occlusion in the Rat

Abstract: The rota-rod and grid-walking tests of motor performance provide quantitative, objective, and reproducible measures of functional impairment of rats following an ischemic insult. These impairments correlate directly with infarct volume and provide information integral to future studies evaluating the effects of potential neuroprotective agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
221
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(241 citation statements)
references
References 31 publications
16
221
1
1
Order By: Relevance
“…Data are expressed as mean7s.d. rats has been shown to cause significant motor impairments, as assessed using the rotarod and grid test (Rogers et al, 1997). This was found, in the present study, to be true also in mice.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Data are expressed as mean7s.d. rats has been shown to cause significant motor impairments, as assessed using the rotarod and grid test (Rogers et al, 1997). This was found, in the present study, to be true also in mice.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, these previous studies give no clue as to any longerterm benefits of G-CSF treatment after stroke. While some argue that infarct size correlates well with certain neurologic deficits (Rogers et al, 1997), this is certainly not always the case (Hattori et al, 2000;Reglodi et al, 2003). Functional outcomes are more useful in terms of assessing the benefit of a treatment after stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Also, preclinical studies have shown that transient middle cerebral artery occlusion (MCA) occlusion plus reperfusion causes less damage than permanent MCA occlusion in rats (Memezawa et al, 1992;Rogers et al, 1997). However, reperfusion carries some risks, such as hemorrhagic transformation and fatal edema, which could be attributed, at least in part, to reperfusion injury (Pan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that the improved behavioral recovery in multiparous females may simply reflect the smaller infarct seen in these mice rather than an enhanced delayed angiogenic response. Behavioral deficits and recovery are known to be related to the location and severity of the initial stroke injury (30,31). However, the near complete preservation of sensorimotor and cognitive function in the multiparous mice is nonetheless impressive, given that the striatal infarct was prominent in both groups.…”
Section: Discussionmentioning
confidence: 99%